Challenges and scope of movement disorder surgery in Nepal - Shrestha, Resha; Gurung, Pritam; Pant, Basant (Nepal Journal of Neuroscience, 2023)
Movement disorders (MD) are clinical syndromes with either excess or paucity of voluntary or involuntary movements without weakness or spasticity. Hypokinetic MD includes primary and secondary Parkinsons disease and Parkinsons syndrome and hyperkinetc MD includes dystonia, tremors, choreas and dyskinesias. Although medical treatment is the mainstay of treatment modality, in selected cases surgical treatment is a safe option